CANNA INDICA (L.): A PLANT WITH POTENTIAL HEALING POWERS: A REVIEW - INDIRA PRIYA DARSINI A; S. SHAMSHAD; M.JOHN PAUL (International Journal of Pharma and Bio Sciences, 2015)
The use of plants as medicines predates written human history. Ethnobotany (the study of traditional human uses of plants) is recognized as an effective way to discover future medicines. In 2001, researchers identified 122 compounds used in modern medicine which were derived from "ethnomedical" plant sources; 80% of these have had an ethnomedical use identical or related to the current use of the active elements of the plant. The plant is a biosynthetic laboratory, not only for chemical compounds, but also a multitude of compounds like glycosides, alkaloids etc. These exert physiological and therapeutic effect. Plants can provide biologically active molecules and lead structures for the development of modified derivatives with enhanced activity and reduced toxicity. The small fraction of flowering plants that have so far been investigated have yielded about 120 therapeutic agents of known structure from about 90 species of plants. According to one estimate only 20% of the plant flora have been studied and 60%of synthetic medicines owe their origin to plants. The medicinal values of many plants have been established and published, but most of them are waiting to be explored till date. Therefore, there is every need to find their uses and to conduct pharmacological studies to discover their medicinal properties .Canna Indica (L.) is a spreading annual herb found throughout India but unfortunately it is one of the neglected plants. Hence, the present review aims to open new avenues for the improvement of medicinal use of Canna Indica for various ailments and to bring the anti-diabetic Medicinal plant to the scientists’ notice, and raise awareness and add value to the resource. This review attempts to highlight the available literature on Canna Indica (L.) with respect to ethno botany, chemical constituents and summary of various pharmacologic activities.